ChatGPT's contributions to the evolution of neurosurgical practice and education: a systematic review of benefits, concerns and limitations - Hakija Bečulić; Emir Begagić; Rasim Skomorac; Anes Mašović; Edin Selimović; Mirza Pojskić (Medicinski glasnik, 2023)
Aim: This study provides a comprehensive review of the current literature on the use of ChatGPT, a generative Artificial Intelligence (AI) tool, in neurosurgery. The study examines potential benefits and limitations of ChatGPT in neurosurgical practice and education. Methods: The study involved a systematic review of the current literature on the use of AI in neurosurgery, with a focus on ChatGPT. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were followed to ensure a comprehensive and transparent review process. Thirteen studies met the inclusion criteria and were included in the final analysis. The data extracted from the included studies were analysed and synthesized to provide an overview of the current state of research on the use of ChatGPT in neurosurgery. Results: The ChatGPT showed a potential to complement and enhance neurosurgical practice. However, there are risks and limitations associated with its use, including question format limitations, validation challenges, and algorithmic bias. The study highlights the importance of validating machine-generated content for accuracy and addressing ethical concerns associated with AI technologies. The study also identifies potential benefits of ChatGPT, such as providing personalized treatment plans, supporting surgical planning and navigation, and enhancing large data processing efficiency and accuracy. Conclusion: The integration of AI technologies into neurosurgery should be approached with caution and careful consideration of ethical and validation issues. Continued research and development of AI tools in neurosurgery can help us further understand their potential benefits and limitations.
Keywords: artificial intelligence; Ethics; machine learning; decision support systems